Take quenching oil to retrieve filtering capability's impacter guenching unit - YANG YUEFEI; ZHAO JIDUAN; JIA LIGANG; ZHOU BIN; TANG HUIDE (2018)
The utility model discloses a take quenching oil to retrieve filtering capability's impacter guenching unit, including oil quenching tank, the groove of stewing, oil -well pump, first filter and hoisting accessory, oil quenching tank is provided with the oil inlet, it is provided with the oil -out to stew the groove, first filter is connected to oil -well pump one end, first filter intercommunication oil inlet, and the other end of oil -well pump communicates the oil -out, hoisting accessory sets up in the top of stewing groove and oil quenching tank, hoisting accessory includes at least one guide rail, can follow the mobile device and the pulley gear of guide rail action, and the pulley gear setting is in the mobile device below, and the pulley gear is including drive arrangement and at least one wheelset, and drive arrangement fixes on the mobile device, and the wheelset passes through chain drive with drive arrangement and is connected. The utility model discloses a take quenching oil to retrieve filtering